The Role of Waqf in Supporting Sustainable Development Goals: Linking theory and its practices - Karimah, Diva Azka; Pamuncak, Mohammad Bintang; Mubin, Muhammad Khoerul (Universitas Muhammadiyah Surakarta, 2023)
Poverty has become a main issue faced by many developing countries. It is worsened by the fact that a few rich people have equal wealth to most of the world's population. Hence attempts to reduce the poverty number have been initiated by many players including academicians and international organizations such as the United Nations through the United Nations Development Program (UNDP). On the other hand, Islamic philanthropy such as Waqf has been linked as a medium to not only eradicate poverty but also attempt to develop and empower society. Therefore, this study attempts to link waqf practices and Sustainable development goals (SDGs). This study uses qualitative methods i.e., explanatory studies. This study finds that waqf has similar characteristics with SDGs in at least 7 out of 17 goals of SDGs, including No Poverty goal, zero hunger goal, good health and wealth being goal, quality education goal, affordable and clean energy goal, decent work and economy goal, and industry, innovation, and infrastructure goal. Hence its promotion of the SDGs program is essential and undeniable. Future studies are encouraged to look further at the potential applications and practices of Waqf to the SDGs, particularly from the perspective of public policy and law.